Amusement Leaves the Port: Pleasure Institutions and the Reshaping of Gothenburg's Material and Nonmaterial Borders, 1860s-1923. (November 2022) - Reimann, Christina
Spaces of pleasure tend to unite people and bridge sociocultural boundaries while involving exclusion mechanisms and tools for social control. Institutions of pleasure also contribute to the spatial configuration of cities. This article explores the role played by pleasure institutions in marking material and nonmaterial borders in turn-of-the-century Gothenburg. It examines how internal city borders, and, in particular, those between areas seen as "port districts" and those conceived as the "city centre, " were constructed, maintained, and given meaning through institutions of pleasure, and how these borders in turn shaped the city's pleasure culture. Analyzing different social actors' share in the social practices and discourses that constructed these borders, I argue that pleasure institutions played an important role in the reconfiguration of Gothenburg's urban space in the course of the city's tension-fraught entry into urban modernity.